1964
DOI: 10.1161/01.res.15.3.258
|View full text |Cite
|
Sign up to set email alerts
|

Transthoracic Ventricular Defibrillation with Square-wave Stimuli: One-Half Cycle, One Cycle, and Multicycle Waveforms

Abstract: A very high powered amplifier for experimental transthoracic ventricular defibrillation has been described. The effectiveness of both one-half-cycle unidirectional and one-cycle bidirectional square waves in terminating ventricular fibrillation first increases, then reaches a maximum and finally decreases as the duration of the shock is increased. With 10- and 20-ampere unidirectional shocks and 10-ampere bidirectional shocks, a maximal effectiveness of substantially 100% was found under the chosen experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1969
1969
2009
2009

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In any case, rectangular stimulation may not extend to sinusoidal waveforms, since rectangular pulses contain a considerable amount of their energy at frequencies higher than their fundamental frequency. Schuder et al 14 reported a clear defibrillation maximum at 128 Hz, but his defibrillation apparatus distorted the waveforms for his next higher point at 256 Hz. For sinusoidal, epicardial stimulation, Witzel et al 15 reported a defibrillation threshold minimum at 60 Hz for sinusoidal waveforms for epicardial, saline-soaked electrodes.…”
Section: Discussionmentioning
confidence: 99%
“…In any case, rectangular stimulation may not extend to sinusoidal waveforms, since rectangular pulses contain a considerable amount of their energy at frequencies higher than their fundamental frequency. Schuder et al 14 reported a clear defibrillation maximum at 128 Hz, but his defibrillation apparatus distorted the waveforms for his next higher point at 256 Hz. For sinusoidal, epicardial stimulation, Witzel et al 15 reported a defibrillation threshold minimum at 60 Hz for sinusoidal waveforms for epicardial, saline-soaked electrodes.…”
Section: Discussionmentioning
confidence: 99%
“…Subject to certain assumptions, the question was answered on theoretical grounds in a paper presented at the 1975 Purdue Cardiac Conference. '*'^ in a 1979 article in Circulation,^" and, with particular emphasis upon implanted systems, in a 1991 article.^' We concluded that if the linear dimensions of the electrodes are scaled hy and the instantaneous current hy (1) (2) then tbe time varying current density vector at corresponding points within the animals will he everywhere identical [primed symbols refer to larger animals/systems; unprimed refer to smaller; d = linear dimensions, m = mass or weight, and I = instantaneous current).…”
Section: Scalingmentioning
confidence: 98%
“…Early devices used a pulse of a single polarity, derived by charging a capacitor, then discharging it through the electrode system (60,74). Research in animals (70), based on previous results in transthoracic defibrillation (72) and isolated cell cultures (41), showed that bidirectional or biphasic pulses ( Figure 2) are safer and more efficacious than the monophasic pulses, defibrillating with lower energies and with potentially less tissue damage. A prospective, randomized trial of biphasic vs monophasic waveforms in humans found that the stored energy defibrillation threshold for monophasic shocks was 8.5 ‫ע‬ 6.1 J and for biphasic shocks was 6.3 ‫ע‬ 5.2 J, lower by 26% (9).…”
Section: Waveformsmentioning
confidence: 99%